THE SELECTION OF ACQUISITION STRATEGY AND SOLVING TRADE SURPLUSES OF FOOD PRODUCTS BY USING THE SIMULATION - Mikić, Neven; Ljubanović Ralević, Ivana; Rajić, Zoran (Economics of Agriculture, 2015)
Real business environment opens up many possibilities of business conduct, so that appropriate strategies, compatible with multicriteria requirements of the environment, potentially lead to the realization of the set goal. Adequate schedule and the optimal combination of available resources are possible to establish by a mathematical formalization in terms of the theoretical model that connects business outcomes with a cause or a probability of their occurrence. Exactly research of the possibility of using and applying the results of theoretical models in solving the specific tasks in regard to expressing relations of initial assumptions related to selection of the optimal operating strategy, is the initial motive of this paper. The theoretical models, which describe the real problem, can be analysed analytically or by simulation, depending on its complexity and the variables type, which describe it. The model should provide achieving the managing balance through the model correction of the available operational resources, increasing in that way also the capacity of decision-making system in terms of futuristic knowledge insufficiency. The research results should show that the simulation model apply, in this particular example, enables to a company significant increase of business efficiency level, more complex utilization of the capacities, increase of the competitiveness, etc.